ARCH_DATA APK: Mobile computing in the service of archaeological research - Malaperdas , George (Journal of Greek Archaeology, 2024)
The ARCH_DATA application is a mobile computing application developed with the aim of creating a more manageable and simplified process of data collection through archaeological field survey. The name comes from ‘Archaeological Data’ and refers to the application’s archaeological survey functions. It’s a program for collecting, analyzing, and maintaining all of the field survey’s data – archaeological, cultural, and environmental. Furthermore, it creates a geospatial archaeological database that is simple to integrate into a GIS environment. The ARCH_DATA application has a number of benefits, first and foremost its simplicity of use. Like all mobile applications, it only requires the user to have a mobile device as their primary logging device. It adapts to the requirements of each archaeological survey by simply modifying the fields of interest to correspond to the demands of each team. There is no limit to the number of entries a user can import, and there is no restriction on the number of people who can use the app at the same time.